A survey of global radiation damage to 15 different protein crystal types at room temperature: a new decay model. (26th December 2012) - Leal, Ricardo Miguel Ferraz; Bourenkov, Gleb; Russi, Silvia; Popov, Alexander N.
<x xml:space="preserve">Abstract</x> The radiation damage rates to crystals of 15 model macromolecular structures were studied using an automated radiation sensitivity characterization procedure. The diffracted intensity variation with dose is described by a two‐parameter model. This model includes a strong resolution‐independent decay specific to room‐temperature measurements along with a linear increase in overall Debye–Waller factors. An equivalent representation of sensitivity via a single parameter, normalized half‐dose, is introduced. This parameter varies by an order of magnitude between the different structures studied. The data show a correlation of crystal radiation sensitivity with crystal solvent content but no dose‐rate dependency was detected in the range 0.05–300 kGy s−1. The results of the crystal characterization are suitable for either optimal planning of room‐temperature data collection or in situ crystallization plate screening experiments.